Future opportunities and trends for e-infrastructures and life sciences: going beyond the grid to enable life science data analysis - Duarte, Afonso M. S.; Psomopoulos, Fotis E.; Blanchet, Christophe; Bonvin, Alexandre M. J. J.; Corpas, Manuel; Franc, Alain; Jimenez, Rafael C.; de Lucas, Jesus M.; Nyrönen, Tommi; Sipos, Gergely; Suhr, Stephanie B. (Frontiers in Genetics, 2015)
With the increasingly rapid growth of data in Life Sciences we are witnessing a major transition in the way research is conducted, from hypothesis-driven studies to data-driven simulations of whole systems. In the context of the European Grid Infrastructure Community Forum 2014 (Helsinki, 19–23 May 2014), a workshop was held aimed at understanding the state of the art of Grid/Cloud computing in EU research as viewed from within the field of Life Sciences. The workshop brought together Life Science researchers and infrastructure providers from around Europe and facilitated networking between them within the context of EGI. The first part of the workshop included talks from key infrastructures and projects within the Life Sciences community. This was complemented by technical talks that established the key aspects present in major research approaches. Finally, the discussion phase provided significant insights into the road ahead with proposals for possible collaborations and suggestions for future actions.